Laboratory Evaluation of Oviposition Behavior of Field Collected Aedes Mosquitoes. (1st July 2014) - Panigrahi, Subrat K.; Barik, Tapan K.; Mohanty, Satyabrata; Tripathy, Niraj Kanti
Abstract : Wild female Aedes aegypti and Ae . albopictus were allowed to lay eggs in (i) ovitraps with different concentrations of NaCl, (ii) different coloured ovistrips, (iii) water from different sources, (iv) larva holding water, and different sized ovitraps for oviposition preference. Oviposition cycle was also studied in different photoperiod regimens. The number of eggs laid was observed to gradually decrease with increase in NaCl concentration in both the species. Experiments were conducted to determine egg laying preference for any specific colour of the ovistrip and black ovistrip was found to be most preferred by both the species. For oviposition preference, eight water samples collected from different sources were used and it was observed that the maximum number of eggs was laid in ovitraps containing distilled water followed by tap water. In addition, Aedes mosquitoes laid more number of eggs in ovitraps containing larval holding water than ovitraps containing distilled water. Further, both the species did not lay any egg in the smallest used ovitrap although the number of eggs was maximally deposited in the largest ovitrap used. In the present studies, both the Aedes species laid the maximum number of eggs in the 4th quarter of the light period with normal 12 h light and dark phases (LD 12 : 12).